Evaluation of the influence of uncertainty between predicted and measured ground water and in-situ stress on the stability of a large open pit using a three dimensional distinct element method - Hamdi, P.; Griffiths, Cedric; D'Ambra, S. (2017)
© 2017 ARMA, American Rock Mechanics Association. This study focuses on the use of a predictive three dimensional distinct element numerical model to assess the potential for large-scale failure mechanisms at a diamond mine in Canada. The upper portion of the kimberlite pipe has been exploited by traditional open pit mining method and currently mining continues underground beneath open pit with a vertical glory hole extending down to the active underground mining levels. Underground mining adopts sub-level retreat (SLR) methods. The objective of this study is to assess the stability of the open pit as underground mining progresses. The influence of uncertainties in two key input parameters, the in-situ stress field and groundwater pressures, was evaluated using a three dimensional Distinct Element Method software 3DEC. A hydrogeological model has been developed to evaluate groundwater pressures and flows at the mine site. In-situ stress testing has been carried out to confirm a historical in-situ stress field based on the understanding of the tectonic history and geological settings. Sensitivity analyses have been carried out to determine the influence of these two key parameters on the stability of an identified critical wedge in the pit wall. The potential impact of groundwater depressurization on stability of the identified critical wedge is also evaluated.